Lumen Apposing Metal Stents (LAMSs) for Drainage of Pancreatic and Gallbladder Collections: A Meta-analysis. Issue 9 (October 2018) - Han, Dennis; Inamdar, Sumant; Lee, Calvin W.; Miller, Larry S.; Trindade, Arvind J.; Sejpal, Divyesh V.
Abstract : Background and Aims: Endoscopic ultrasound-guided transmural drainage using lumen apposing metal stents (LAMSs) is becoming a popular and promising therapeutic approach for drainage of intra-abdominal fluid collections. There has been an increasing number of studies evaluating LAMS for drainage of pancreatic pseudocysts (PP), walled-off pancreatic necrosis (WOPN), and gallbladder (GB) drainage. The aim of this meta-analysis is to analyze the literature to date regarding the clinical success, technical success, and adverse events of LAMS in treatment of pancreatic fluid collections and GB drainage. Methods: A comprehensive search of multiple literature databases through November 2016 was performed. Human studies with at least 10 subjects that examined the clinical success, technical success, and adverse events of LAMS in treating PP, WOPN, and GB drainage were included. Results: A total of 993 patients (608—WOPN; 204—PP; 181—GB drainage) underwent drainage from 20 trials. For drainage of WOPN, the pooled technical success was 98.9% [95% confidence interval (CI): 98.2% to 99.7%] and clinical success was 90% (95% CI: 87% to 93%) (τ 2 =0.001). For drainage of PP, the pooled technical success was 97% (95% CI: 95% to 99%) and clinical success was 98% (95% CI: 96% to 100%), (τ 2 =0.001). For GB drainage, the pooled technical success was 95% (95% CI: 91% to 99%) and clinical success was 93% (95% CI: 90% to 97%), (τ 2 =0.001). Total adverse events occurred in 11% of patients with higher complication rates observed in GB drainage. There was no evidence of publication bias in this meta-analysis. Conclusions: Endoscopic ultrasound-guided transmural drainage using LAMS is becoming a widely accepted therapeutic approach for the treatment of PP, WOPN, and GB drainage with high clinical and technical success rates and acceptable adverse events. Further prospective randomized trials reporting long-term clinical efficacy and cost-effectiveness are needed to validate LAMS as a therapeutic modality for pancreatic and GB collections. Abstract : Supplemental Digital Content is available in the text.